Pericardial Effusion in Association With Periodontitis: Case Report and Review of 8 Patients in Literature - Toshihiko Matsuo MD, PhD; Chie Nakago Matsuo DDS, PhD; Nobuhiko Matsuo MD, PhD; Ayano Mori DDS, PhD; Masaaki Murakami MD, PhD; Hiroshi Ito MD, PhD (SAGE Publishing, 2024)
Periodontal diseases are well-known background for infective endocarditis. Here, we show that pericardial effusion or pericarditis might have origin also in periodontal diseases. An 86-year-old man with well-controlled hypertension and diabetes mellitus developed asymptomatic increase in pericardial effusion. Two weeks previously, he took oral new quinolone antibiotics for a week because he had painful periodontitis along a dental bridge in the mandibular teeth on the right side and presented cheek swelling. The sputum was positive for Streptococcus species. He was healthy and had a small volume of pericardial effusion for the previous 5 years after drug-eluting coronary stents were inserted at the left anterior descending branch 10 years previously. The differential diagnoses listed for pericardial effusion were infection including tuberculosis, autoimmune diseases, and metastatic malignancy. Thoracic to pelvic computed tomographic scan demonstrated no mass lesions, except for pericardial effusion and a small volume of pleural effusion on the left side. Fluorodeoxyglucose positron emission tomography disclosed many spotty uptakes in the pericardial effusion. The patient denied pericardiocentesis, based on his evaluation of the risk of the procedure. He was thus discharged in several days and followed at outpatient clinic. He underwent dental treatment and pericardial effusion resolved completely in a month. He was healthy in 6 years until the last follow-up at the age of 92 years. We also reviewed 8 patients with pericarditis in association with periodontal diseases in the literature to reveal that periodontal diseases would be the background for developing infective pericarditis and also mediastinitis on some occasions.